Comparison of the effects and mechanisms of astaxanthin, astaxanthin esters and astacene on high-fat diet-induced NAFLD - Chunhao Gao; Fangtian Chen; Nengyun Gong; Shiran Hu; Mengjia Zhu; Qingxin Zhou; Xiang Gao (Journal of Functional Foods)
Non-alcoholic fatty liver disease (NAFLD) represents a global health challenge with limited therapeutic options. This study compared the efficacy and mechanisms of astaxanthin (AX), astaxanthin esters (AXE), and astacene (AC) in ameliorating high-fat diet-induced NAFLD in mice. The three supplements improved liver function, and reduced hepatic lipid accumulation, liver injury, serum lipid levels, HOMA-IR index in NAFLD mice. Notably, AXE exhibited slightly better trends. Mechanistically, they activated the hepatic Nrf2/Keap1 antioxidant pathway. Gut microbiota analysis suggested that improvements in gut microbiota dysbiosis might partly elucidate their protective mechanisms on NAFLD, with AC exhibiting superior efficacy. Moreover, transcriptome sequencing analysis indicated that AX primarily regulates gene transcription in adipose tissue and AC exhibited the most potent regulatory impact on gene transcription in liver. While AXE displayed notable efficacy in modulating transcriptional profiles across both tissues. This study provides novel insights into the effects of astaxanthin derivatives in ameliorating NAFLD